2001
DOI: 10.1007/s00134-001-1159-4
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus intermittent renal replacement therapy: a meta-analysis

Abstract: Current evidence is insufficient to draw strong conclusions regarding the mode of replacement therapy for acute renal failure in the critically ill. However, the life-saving potential with CRRT suggested in our secondary analyses warrants further investigation by a large, randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
142
1
22

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(169 citation statements)
references
References 26 publications
4
142
1
22
Order By: Relevance
“…Two RCTs comparing IRRT with CRRT in ARF have been published, and these report results that are inconclusive for the major end-point [8,9], and a further RCT is underway in France [10]. A recent meta-analysis using randomized or observational studies suggested that CRRT is associated with a lower rate of hospital mortality than IRRT [11]. In the present study we extracted from our large database [2] those ARF patients who required RRT with the following two specific objectives: (a) to describe the characteristics of the patients according to the RRT modality used and (b) to assess the extent to which the RRT mode affects patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Two RCTs comparing IRRT with CRRT in ARF have been published, and these report results that are inconclusive for the major end-point [8,9], and a further RCT is underway in France [10]. A recent meta-analysis using randomized or observational studies suggested that CRRT is associated with a lower rate of hospital mortality than IRRT [11]. In the present study we extracted from our large database [2] those ARF patients who required RRT with the following two specific objectives: (a) to describe the characteristics of the patients according to the RRT modality used and (b) to assess the extent to which the RRT mode affects patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…der Letalität von Patienten, welche mit kontinuierlichen (CVVH) vs. intermittierenden (IHD) Nierenersatzverfahren behandelt worden waren [23,37]. Es fand sich selbst dann kein Unterschied, wenn ausschließlich randomisierte Studien berücksichtigt wurden [37].…”
Section: Kontinuierliche Vs Intermittierende Nierenersatzverfahrenunclassified
“…We sentliche Veränderungen erfuhren auch die Therapiekonzepte in Bezug auf den "optimalen" Zeitpunkt für den Beginn einer Therapie bei einsetzendem ANV und in Bezug auf die Empfehlungen für die Dosierungen [6]. Dennoch sind evi denzbasierte Richtlinien zur Behandlung des ANV mit extrakorporalen Nierener satzverfahren derzeit aus Mangel an ent sprechenden randomisierten kontrollier ten Studien nicht verfügbar [7].…”
Section: Nierenersatzverfahren Auf Der Intensivstationunclassified